Comparing an interdependent and dependent group contingency to increase physical activity in students during recess. (13th October 2022) - Asaro, Madeline M.; Zonneveld, Kimberley L. M.; Frijters, Jan C.
Abstract: Physical activity produces important physiological, mental health, academic, and cognitive benefits in children and youth. Despite these advantages, a large proportion of this population does not meet the recommended amount of physical activity. Recent studies have shown that the interdependent (IGC) and dependent (DGC) group contingencies improve physical activity; however, no comparison of the effects of these contingencies on physical activity has been conducted. We used a multielement within a concurrent multiple baseline design across three classes to compare the effectiveness of group contingencies on physical activity. Both group contingencies increased physical activity, with the IGC producing slightly higher overall levels of physical activity at the classwide and individual levels of analyses. We also compared participants' positive and negative statements and found that, regardless of the group contingency in effect, participants emitted higher levels of positive statements about the contingency when they earned the reward than when they did not, suggesting that reward delivery influenced statements more so than the group contingency arrangement. Results are discussed within the context of treatment decisions and future research.